2011
DOI: 10.1073/pnas.1014935108
|View full text |Cite
|
Sign up to set email alerts
|

Neuroanatomical dissociation for taxonomic and thematic knowledge in the human brain

Abstract: It is thought that semantic memory represents taxonomic information differently from thematic information. This study investigated the neural basis for the taxonomic-thematic distinction in a unique way. We gathered picture-naming errors from 86 individuals with poststroke language impairment (aphasia). Error rates were determined separately for taxonomic errors ("pear" in response to apple) and thematic errors ("worm" in response to apple), and their shared variance was regressed out of each measure. With the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

33
271
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 253 publications
(316 citation statements)
references
References 48 publications
33
271
3
Order By: Relevance
“…Taxonomic relationships appear to activate neural bases that are commonly reported when perceptual processing is engaged (i.e., visual associated areas, bilaterally), whereas thematic relationships recruit a bilateral temporoparietal network (Kalénine et al, 2009). It is worth noting that the involvement of the temporoparietal junction -known to be involved in motion, action and spatial processing -has been consistently revealed across several studies (de Zubicaray et al, 2013;Mirman and Grazanio, 2012b;Schwartz et al, 2011). Concerning the neural correlates of semantic priming for taxonomic and thematic relationships in lexical-decision tasks, several fMRI studies (Kotz et al, 2002;Sachs et al, 2008b;Sass et al, 2009) revealed that taxonomic relationships require the recruitment of additional areas in the right hemisphere, interpreted as reflecting a more effortful semantic processing than for thematic one.…”
Section: Discussionmentioning
confidence: 99%
“…Taxonomic relationships appear to activate neural bases that are commonly reported when perceptual processing is engaged (i.e., visual associated areas, bilaterally), whereas thematic relationships recruit a bilateral temporoparietal network (Kalénine et al, 2009). It is worth noting that the involvement of the temporoparietal junction -known to be involved in motion, action and spatial processing -has been consistently revealed across several studies (de Zubicaray et al, 2013;Mirman and Grazanio, 2012b;Schwartz et al, 2011). Concerning the neural correlates of semantic priming for taxonomic and thematic relationships in lexical-decision tasks, several fMRI studies (Kotz et al, 2002;Sachs et al, 2008b;Sass et al, 2009) revealed that taxonomic relationships require the recruitment of additional areas in the right hemisphere, interpreted as reflecting a more effortful semantic processing than for thematic one.…”
Section: Discussionmentioning
confidence: 99%
“…Most research has focused on concrete concepts, showing that semantic category and association both play a key role in representing concrete concepts (e.g., Kalénine et al, 2009;Sachs, Weis, Krings, Huber, & Kircher, 2008;Sachs, et al, 2011;Schwartz, et al, 2011; for reviews, see Hutchison, 2003;Mahon & Caramazza, 2009;Martin, 2007), but the representations of abstract concepts are less explored. The recent different representational frameworks theory proposes that category and association are important for representing both concrete and abstract words but concrete words rely more on category whereas abstract words rely more on association (Crutch & Warrington, 2005.…”
Section: Introductionmentioning
confidence: 99%
“…The general consensus is that taxonomic and thematic relations rely on two functionally distinct, but complementary, modes of conceptual organization in semantic memory. The dissociation of taxonomic versus thematic processing has been documented in behavioral (Borghi & Caramelli, 2003;Lin & Murphy, 2001;Masuda & Nisbett, 2001;Mirman & Graziano, 2012), neuroimaging (Kalénine, Mirman, & Buxbaum, 2012;Sachs, Weis, Krings, Huber, & Kircher, 2008;Schwartz et al, 2011), and patient (Davidoff & Roberson, 2004) studies. Furthermore, thematic processing has been shown to be as crucial in language comprehension, analogy making, similarity judgment, and memory processes as is taxonomic knowledge (for a review, see Estes et al, 2011).…”
mentioning
confidence: 99%